The Impact of Social Media Platforms On Sichuan Consumers' Purchase Behavior in the Catering Services - Kaizhou Ma; Jacky Mong Kwan Watt (Global Management: International Journal of Management Science and Entrepreneurship, 2025)
The rapid advancement of digital technology has transformed the landscape of marketing, with social media platforms emerging as powerful tools for influencing consumer behavior. This study aims to examine the impact of social media engagement, content quality, and social proof on the purchasing behavior of consumers in the catering services industry in Sichuan, China. Recognizing the dynamic nature of the digital marketplace, the research adopts a quantitative approach, utilizing a structured survey to gather data from 390 participants who are active users of social media and potential consumers of catering services. Statistical analysis reveals a significant and positive correlation between all three independent variables—social media engagement, content quality, and social proof—and consumers’ likelihood to purchase catering services. Specifically, higher levels of engagement, such as